Cserépfalu melletti fás legelő vegetációjának változása - Penksza, Károly; Saláta, Dénes (Gyepgazdálkodási Közlemények, 2022)
The wood-pastures were important elements of the landscape, moreover had apprecieable act in the agriculture. This type of management belongs to the ’agroforestry’ systems which are really ancient agricultural land uses, but nowadays endangered woody habitats in Hungary. The aim of our study was to collect, data about the appearance and traceability of different factors on the vegetation at different parts of a wood pasture.